Current Concepts in Premature Ovarian Insufficiency. (March 2015) - Maclaran, Kate; Panay, Nick
Premature ovarian insufficiency (POI) is a life-changing diagnosis, with profound physical and psychological consequences. Unfortunately, there are many deficiencies in our understanding of the condition as the underlying etiology and optimum management strategies are poorly understood. Improved awareness of POI and its long-term implications has led to increased research interest in recent years. Current research has allowed a greater understanding of the changing epidemiology in POI, genetic factors in its etiology and randomized controlled trials of hormone therapy are underway to provide evidence for treatment. This article reviews the latest literature on POI to summarize current understanding and future directions.